Analisis Beberapa Sifat Fisikokimia dari Minyak Goreng Kemasan Hasil Penggorengan Ubi Jalar (Ipomea batatas) - Sabrina, Joya; Dewata, Indang; Oktavia, Budhi; Pernadi, Niza Lian; Farhan, Muhammad; Rahmi, Fathaniah Raviqa; Nizar, Umar Kalmar (Departemen Kimia FMIPA UNP, 2024)
Cooking oil is a biological mixture derived from plants and consists of a mixture of esters derived from glycerol with fatty acids. The most commonly used cooking oil for cooking by the community is palm oil, because it is easy to obtain and the price is relatively affordable. The main composition of palm oil is triglycerides more than 95% and several other components such as monoglycerides, diglycerides, free fatty acids, phosphatides and sterols. Sweet Potatoes have the main content, namely carbohydrates. In addition to carbohydrates, there are other ingredients such as protein and fat. The purpose of this study was to determine the physicochemical properties of packaged cooking oil from sweet potato frying at a certain time and temperature and to use packaged cooking oil without heating as a comparison. The physicochemical properties of the oil determined include density, flow rate, acid number and saponification number. Bimoli cooking oil from sweet potato frying has a density value of 0.9369 gr/ml, a flow rate of 3.662 ml/s, an acid number of 8.143 mgKOH/gr and a saponification number of 14.305 mgKOH/gr. The results of this study indicate that the results of the physicochemical properties test of packaged cooking oil have a better value than the test results of sweet potato frying oil.